THE PRACTICE OF GENRE-BASED PEDAGOGY IN INDONESIAN SCHOOLS: A CASE OF PRESERVICE TEACHERS IN BANDUNG, WEST JAVA PROVINCE - Nurlaelawati, Iyen; Novianti, Nita (Universitas Pendidikan Indonesia, 2017)
This paper reports preservice teachers’ knowledge and understanding about genre-based pedagogy in the curriculum and its implementation in their EFL classrooms. Six participants who were taking their teaching practicum program in two different state schools took part in the study. Employing a case study design, the data were collected through questionnaire, observations, interviews, and document analysis (lesson plans). The findings show that the preservice teachers had varying degrees of knowledge and understanding of what genre-based pedagogy is and how to apply it in the teaching and learning. All of them, though, believe that genre-based pedagogy is very useful and applicable in EFL teaching and learning. Out of the six participants, four employed the pedagogy in their classroom teaching and learning. There is, however, a gap between what the preservice teachers know and understand about genre-based pedagogy and how they apply it in the classroom. Most of the preservice teachers skip the most important part in genre-based pedagogy, namely building knowledge of the field. They also do not give feedback to their students’ writing. These findings have some implications for the English teacher education in Indonesia. Teacher education institutes should pay more attention on preservice teachers’ practices in the classroom. Cooperation between the teacher supervisor, lecturer, and preservice teachers is really needed.